Effects of nano guano, nano phosphate rock, and SP-36 fertilizers on maize growth and phosphorus uptake in inceptisol - Nia Herlina; Sri Nuryani Hidayah Utami; Cahyo Wulandari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2022)
Nanotechnology fertilizers are fertilizers associated with objects measuring 1 nm to 100 nm capable of controlling or manipulating at an atomic scale. Phosphorus is one of the essential nutrients needed by plants in large amounts. Maize is a strategic commodity requiring optimal nutrients. Inceptisol is soil that has relatively low fertility and chemical properties. The addition of P nutrients to the soil plays an important role in improving soil quality. This study aimed to compare the types of P fertilizers of nano guano, nano phosphate rock, and SP-36 with various doses of P2O5 and determine the most effective type. This research was arranged in a completely randomized design (CRD) with two factors. The first factor is the type of fertilizer, consisting of nano guano, nano phosphate rock, and SP-36. The second factor is the dose of P2O5 with four treatment levels, namely 0 kg.ha-1, 50 kg.ha-1, 100 kg.ha-1, and 150 kg.ha-1. The results showed that nano phosphate rock was the most effective fertilizer for maize in Inceptisol. The optimum dose of P fertilizer was 100 kg.ha-1, which was able to produce the highest plant height (215.67 cm) and phosphorus uptake (0.4765 g/plant).